Trends in Snacking Among U.S. Children (2010)
Nationally representative surveys of food intake in US children show large snacking increases between the 1989–91 to 1994–98 and 1994–98 to 2003–06 periods. Childhood snacking trends are moving toward three snacks per day with over 27% of daily calories coming from snacks. The largest increases have been in salty snack and candy consumption, while desserts and sweetened beverages remain the major sources of calories from snacks.